Kajian Literatur Analisis Efisiensi Rantai Pasok Cabai Merah: Integrasi Studi di Berbagai Wilayah Indonesia - Anggun Fitri Aulia; Ismail Hammam Wira Kusumoe; Agustin Ambarwati; Syahla Ameera Savitri Siradju; Wien Kuntari (INDO PUBLISHING, 2026)
This study aims to analyze the structure and patterns of red chili marketing channels across various regions in Indonesia, compare the level of marketing efficiency in terms of marketing margins, distribution of profits among marketing institutions, and the percentage of prices received by farmers (farmer’s share), as well as identify the main factors that hinder the efficiency of the red chili supply chain. This research employs a descriptive approach through a literature review to analyze the structure and performance of the red chili supply chain in Indonesia. The results indicate that the marketing channel structure, which involves many intermediaries—including distribution to Pasar Induk Kramat Jati—affects the length of the supply chain, marketing margins, and the size of the farmer’s share. The supply chain faces several key challenges, including climate uncertainty, limited capital, simultaneous planting patterns, long distribution channels, weak formal contracts, and information asymmetry. System efficiency is not only determined by profit and return on investment (ROI), but also by the proportion of prices received by farmers. In general, shorter supply chains tend to produce lower marketing margins and higher farmer’s share compared to longer and more complex chains.